From agency to root causes: addressing structural Barriers to transformative justice in transitional and post-conflict settings. Issue 5 (23rd November 2020) - Hoddy, Eric T.; Gready, Paul
ABSTRACT: Transformative justice has emerged as a new practice agenda for addressing structural and systemic violence in post-conflict and post-authoritarian societies. This article is situated at a critical juncture: while the emerging scholarship has focussed on community agency and action, there is little as yet that has explored the social structures and relations in transition societies that are harm-generating and which constrain action. We argue that a critical social science, grounded in realist social theory, systems thinking and complexity theory, have a vital role to play in rendering transparent the relations and structures that resist change. New knowledge about the 'root causes' of harm is both conceptually innovative and useful to practice, helping practitioners identify societal arrangements in need of change and informing strategies for action. This article illustrates the approach through its application to a study with poor farmers in post-Revolution Tunisia. The article should be of interest to researchers and practitioners in transitional and transformative justice, conflict and post-conflict, peacebuilding, and security sector reform, who are engaged with understanding and addressing issues of structural and systemic violence.